2016
DOI: 10.20529/ijme.2017.003
|View full text |Cite
|
Sign up to set email alerts
|

Ethical attitudes of nursing students at Shahid Beheshti University of Medical Sciences, Iran

Abstract: An ethical attitude denotes motivation and commitment in practice and is an important aspect of human communication. Values guide the efforts of human beings towards helping those in need, and an ethical attitude revives values and turns them into action. As a result, an ethical attitude and a sense of responsibility have direct effects on ethical action and ultimately, on the outcome of patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 0 publications
2
18
1
3
Order By: Relevance
“…Ethical attitude and a sense of responsibility have direct effects on ethical action and ultimately on the outcome of patient care (19). Seif et al, in their study, demonstrated that medical professionals working in the health care system have an unfavorable theoretical knowledge about medical professionalism in Iran, although this does not indicate that their practices are unethical.…”
Section: Discussionmentioning
confidence: 99%
“…Ethical attitude and a sense of responsibility have direct effects on ethical action and ultimately on the outcome of patient care (19). Seif et al, in their study, demonstrated that medical professionals working in the health care system have an unfavorable theoretical knowledge about medical professionalism in Iran, although this does not indicate that their practices are unethical.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with studies conducted by studies of some authors. [ 7 20 21 ] By the use of this workplace teaching, which was applied in this study, it would be expected that participants' attitudes will change. In another study on the study of ethics teaching by Choi et al .…”
Section: Discussionmentioning
confidence: 99%
“…This is because the instructors are those who transfer their knowledge and experience to students through applying effective communication strategies. So, it can be said that the instructors are the linking bridge between theory and clinical practice (Moosavi et al, 2017). Hence, in planning effective programs for improving clinical training, special attention should be given to trainers and their performance (Baraz Pordanjani et al, 2009).…”
Section: Discussionmentioning
confidence: 99%